Effect of Peanut Addition (Arachis hypogea) On Organoleptic Properties, Nutritional Value, and AcceptabilitySnack Peanbars for Pregnant Women in the Working Area - khaerukiatul Rohmi; Made Darawati; AASP Chandradewi; I gde narda Widiada (Poltekkes Kemenkes Mataram, 2023)
Background: Snack bars, which are rectangular and contain all the nutrients humans need, can be a great option to meet the nutritional needs of pregnant women because pregnant women need a balanced and nutrient-rich intake to meet the needs of the fetus and mother. One of the most common health problems in developing countries is malnutrition among pregnant women. One of the efforts to be made is to improve the nutritional status of pregnant women by providing local food-based snacks, namelysnack peanbars.Research Methods: In this study, experiments were conducted using a completely randomized design (CRD), consisting of five treatment levels, by collecting data on organoleptic properties, data on nutrient values, and data on acceptability. Organoleptic quality was analyzed by hedonic test while the nutrient content (moisture content, ash content, protein content, fat content, and carbohydrate content) was tested in the laboratory Research Result: The results showed that adding peanuts significantly affected aroma and texture (p<0.05). The selected products are formulationsSnack Peanbars t4 (42 g peanuts) with nutritional content per 100 grams with Energy 407.8 kcal, protein 8.90 grams, fat 12.40 grams, carbohydrates 65.15 grams, water content 13.07 grams, ash content 0.47 grams. While acceptanceSnack Peanbars in pregnant women, namely 90% good acceptance and 10% poor acceptance. Conclusion: The addition of 75% peanuts (42 g) had a significant effect on the texture and aroma parameters (p<0.05), while the color and taste parameters had no significant impact (p>0.05). Snack Peanbars per 100 g contain an energy of 407 kcal, protein 8.9 g, fat 12.4 g, and carbohydrates 65.15 g—acceptability results peanbars in pregnant women with good acceptance of 90% and less acceptance of 10%.